Women and Part-Time Employment: Workers' 'Choices' and Wage Penalties in Five Industrialized Countries - Elena Bardasi; Janet C. Gornick (Luxembourg Income Study (LIS), 2000)
This paper uses cross-nationally comparable data from the Luxembourg Income Study (LIS) to analyze the patterns and consequences of part-time employment among women across five industrialized countries - Canada, Germany, Italy, the United Kingdom, and the United States - as of the middle 1990s. The results reveal the influence of dependent care responsibilities related to the presence of young children and elderly household members. We also find unadjusted part-time wage penalties everywhere, ranging from 8-12% in Canada and Germany, to 15% in the UK, to as high as 22% in the US and Italy, meaning that part-time workers earn that much less than full-time workers. The sources of the observed wage gaps vary markedly across countries; only in Germany do we find evidence of 'discrimination' against part-time workers.
Keywords: 330; Weibliche Arbeitskräfte; Arbeitsangebot; Teilzeitarbeit; Lohnstruktur; Deutschland; Großbritannien; Italien; Kanada; USA